Analisis Angel Of Take-Off Lompat Jauh Gaya Jongkok Pada Atlet Jawa Tengah Berbasis Biomekanika - Topo Suhartoyo; Tegar Pangudi; Mohammad Nanang Himawan Kusuma; Muhamad Syafei; Arfin Deri Listiandi; Andri Arif Kustiawan (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Angle analysis, especially when athletes take of or focus on the long jump, is important to know as a study material by athletes and coaches in determining the ideal angle. This allows athletes to produce optimal jumps in a championship. The purpose of the study was to analyze the magnitude of the angle in the angel of take off phase in the long jump squat style of central java athletes. This research is a quantitative descriptive study. The time and location of the study in January 2022 was carried out at GOR Soesilo Soedarman. The sampling technique using purposive sampling obtained 15 athletes who met the inclusion and exclusion requirements.The analysis uses the kinovea application to determine the size of the body angle when focusing on the fulcrum board using the help of a camera. The results showed that athletes who produced the highest angle of take-off of 22.7° showed less than optimal results compared to athletes who produced an angle of take-off of 20°-21.8°atthe angle of take-off influenced by the phases in the take-off, namely touchdown, amortization and extension. Athletes who used the lowest angle of take-off (9.6°) also recorded the lowest achievement record of 5.00 meters-5.05 meters. Athletes who used an angle of take-off of 11o produced varying achievements, ranging from 5.09 meters-5.44 meters. The highest achievement was obtained by the sample using an angle of take-off between 20°-21.8° resulting in an achievement of between 6.06 meters -6.22 meters. Meanwhile, athletes who use an angle of take-off of 22.7° produce an achievement of 5.32 meters.